Faktor Pendapatan Pada Pengaruh Audit Internal Terhadap Resiko Kecurangan (Fraud) - Shailla Nisa Lidiawati; Nur Anisa; Dien Noviany Rahmatika (Kajian Ekonomi dan Akuntansi Terapan, 2024)
As a result of this study, cheating can be defined as any action that can be carried out by an individual or group by using fraudulent methods to gain profits. Financial fraud typically involves the misuse of funds obtained through fraud, usually by managers, executives, employees, or third parties, for the purpose of obtaining unlawful profits. In order for financial statements to be used as a basis for decision-making and to be trusted by the public and third parties, we found that the quality of the audit process is very important. This shows that the auditor's experience can affect the impact of fraud risk assessment on the auditor's ability to detect fraud. Previous research has shown that auditor experience can affect the impact of auditors' ability to detect fraud. The purpose of this study is to compare the results of different studies on the impact of fraud on internal audit components.